Decision Making at World Trade Organization: Positive Consensus and its Impact on Developing Countries - Rabia Ilyas; Bilal Khan Tanoli; Kaniz Fatima (Indus Journal of Social Sciences, 2025)
The most striking feature of WTO is the extent to which it preserves the laws and practices of General Agreement on Tariffs and Trades 1947. One of these features is decision making in WTO. Article IX of WTO agreement 1994 provided for voting as well as the consensus rule for decision making. It retains the voting process of GATT but practice of consensus dominates the decision making in WTO. All the decision making in WTO is based on the positive consensus rule that makes it different from other International Organizations. Positive consensus rule require that a decision will be made if all the members present are agreed and do not expressly object on it. It means that every single member State of WTO has veto power and can limit the decision making by raising objection. Although the consensus practice generally works well but there is always a risk of deadlock and in particular the inability of members to respond legislatively where it disagrees with other member States. Consensus rule has many advantages but it is questionable that whether it is more democratic and effective than the majority rule. This doctrinal study analyzes the impact of this rule on developing member states. This paper discusses that whether the consensus practice of WTO benefits the developing states and adequate for making, revising and implementing rules on International Trade. It discusses as how the decision making in WTO can be more effective and inclusive by reviving and incorporating the practice of voting and other reforms.